Drosophotoxicology: Elucidating Kinetic and Dynamic Pathways of Methylmercury Toxicity in a Drosophila Model - Rand, Matthew D.; Vorojeikina, Daria; Peppriell, Ashley; Gunderson, Jakob; Prince, Lisa M. (Frontiers in Genetics, 2019)
The risks of methylmercury (MeHg) toxicity are greatest during early life where it has long been appreciated that the developing nervous system is an especially sensitive target. Yet, understanding the discrete mechanisms of MeHg toxicity have been obscured by the wide variation in the nature and severity of developmental outcomes that are typically seen across individuals in MeHg exposed populations. Some insight has come from studies aimed at identifying a role for genetic background as a modifier of MeHg toxicity, which have predominantly focused on factors influencing MeHg toxicokinetics, notably, polymorphisms in genes related to glutathione (GSH) metabolism. For example, variants in genes encoding the catalytic and modifier subunits of glutamyl-cysteine ligase (GCLc and GCLm), the rate limiting enzyme for GSH synthesis, have been reported to associate with Hg body burden (Hg levels in blood or hair) in humans. However, GSH can facilitate both toxicokinetics and toxicodynamics of MeHg by forming MeHg-GSH conjugates, which are readily transported and excreted, and by acting indirectly as an anti-oxidant, respectively. In this study we refine a model to distinguish kinetic and dynamic traits of MeHg toxicity using a paradigm of Drosophotoxicolgy. First, we identify that the pupal stage is selectively sensitive to MeHg toxicity. Using a protocol of larval feeding, measurements of Hg body burden and assays of development to adulthood (pupal eclosion), we identify strain-dependent variation in MeHg elimination as a potential kinetic determinant of differential tolerance to MeHg. We also find that global upregulation of GSH levels, with GCLc trans-gene expression, can induce MeHg tolerance and reduce Hg body burden. However, we also demonstrate that MeHg tolerance can be achieved independently of reducing Hg body burden, in both wild-derived strains and with targeted expression of GCLc in developing neuronal and muscle tissue, pointing to a robust toxicodynamic mechanism. Our findings have important implications for understanding variation in MeHg toxic potential on an individual basis and for informing the process of relating a measurement of Hg body burden to the potential for adverse developmental outcome.